Perspectives for personalized therapy for patients with multidrug‐resistant tuberculosis. (11th July 2018) - Lange, C.; Alghamdi, W. A.; Al‐Shaer, M. H.; Brighenti, S.; Diacon, A. H.; DiNardo, A. R.; Grobbel, H. P.; Gröschel, M. I.; von Groote‐Bidlingmaier, F.; Hauptmann, M.; Heyckendorf, J.; Köhler, N.; et al.
Abstract: According to the World Health Organization (WHO), tuberculosis is the leading cause of death attributed to a single microbial pathogen worldwide. In addition to the large number of patients affected by tuberculosis, the emergence of Mycobacterium tuberculosis drug‐resistance is complicating tuberculosis control in many high‐burden countries. During the past 5 years, the global number of patients identified with multidrug‐resistant tuberculosis (MDR‐TB), defined as bacillary resistance at least against rifampicin and isoniazid, the two most active drugs in a treatment regimen, has increased by more than 20% annually. Today we experience a historical peak in the number of patients affected by MDR‐TB. The management of MDR‐TB is characterized by delayed diagnosis, uncertainty of the extent of bacillary drug‐resistance, imprecise standardized drug regimens and dosages, very long duration of therapy and high frequency of adverse events which all translate into a poor prognosis for many of the affected patients. Major scientific and technological advances in recent years provide new perspectives through treatment regimens tailor‐made to individual needs. Where available, such personalized treatment has major implications on the treatment outcomes of patients with MDR‐TB. The challenge now is to bring these adances to those patients that need them most. Abstract : Content List ‐ Read more articles from the symposium: "The 10th International Conference on the Pathogenesis of Mycobacterial Infections".